2014
DOI: 10.1123/jpah.2011-0357
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Impact on Grip Strength and Fatigue Resistance: Implications for Exercise and Hand Therapy Practice

Abstract: Smokers demonstrated reduced grip strength and fast fatigability in comparison with nonsmokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…The other test is a swimming test by loading a mass equivalent to a percentage of body weight on the tail for exhaustive swimming based on animal survival instinct [ 7 ]. The grip strength assessment reflects the overall health of the musculoskeletal system and can also be used to evaluate motor-associated coordination and adaption in neurological study [ 30 ]. We found that grip strength could be dose-dependently increased with CCM supplementation ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The other test is a swimming test by loading a mass equivalent to a percentage of body weight on the tail for exhaustive swimming based on animal survival instinct [ 7 ]. The grip strength assessment reflects the overall health of the musculoskeletal system and can also be used to evaluate motor-associated coordination and adaption in neurological study [ 30 ]. We found that grip strength could be dose-dependently increased with CCM supplementation ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since hand-grip strength is influenced by age, 26 smoking status, 11 waist circumference, 27 anemia, 28 hypertension 29 and serum HDL-C levels, 30 Figure 1B).…”
Section: Hand-grip Strength In Copdmentioning
confidence: 99%
“…Reduced hand-grip strength has been associated with smoking in different age groups. 11 To determine whether smoking affects hand-grip strength in the COPD participants, we measured hand-grip strength in the active, exand current smokers with COPD and adjusted it for covariants. Among men, current smokers had lower handgrip strength than the non-smokers of same age groups, as shown among the 55-65 years (…”
Section: Effects Of Smoking Status On Hand-grip Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Detail factors Individual Age, sex, handedness [18]; body position [19]; height and weight, wrist and forearm position [20], [21]; palm length [22]; menopause [23]; menstrual cycle [24]; fitness level [25]; health status [26]; cholesterol level [27]; fatigue [28]; diet [29]; smoking [30], [31], [32]; sleep quality [33] and circadian rhythm [34].…”
Section: Table 1-factors Influencing Hand Grip Strength Domainmentioning
confidence: 99%